How Do We Recognize Recent Sexual Abuse in Children Less than 10 Years of Age? What Is the Role of Paediatric Wards? Experience in a French Paediatric Hospital - Picherot, G.; Vabres, N.; Fleury, J.; Launay, E.; Gras-Leguen, C. (IntechOpen, 2012)
None